Communicative and linguistic abilities of the Wolf-Hirschhorn syndrome: a case study with attenuated phenotype - Martínez López, Verónica; González-Lamuño Leguina, Domingo; Hernández Hernández, Sonia; Ceballos Cayón, Sara; Ortega Quijano, Daniel (Revista de Investigación en Logopedia, 2020)
genetic syndrome caused by a deletion of the short arm of chromosome 4 (4p16.3). They present a variable phenotype with pre and postnatal growth delayed, epilepsy, psychomotor delayed, hypotonia, craniofacial anomalies (facies in "Greek helmet" and occlusive defects), intellectual disability and difficulties in the use of both expressive and comprehensive language. The aim of this study is to describe the communicative and linguistic abilities of a girl with an attenuated phenotype of SWH, both at the level of phonological, morphological and lexical development. A Spanish girl aged 8;08 years diagnosed by SWF using CGHarray, without significant structural orofacial anomalies, except very immature larynx participates in this study. Her linguistic abilities are evaluated in interaction situation for 45 minutes, with standardized tests and registration made by the parents. The frequency and nature of production errors in terms of phonological processes are analyzed. The results show that her receptive language skills are equivalent to those of children of 3;08 years old. In situation of interaction produces less than 50 words. She has not acquired all the Spanish phonetic repertoire. The frequency of phonological processes is very high and typical of children who are in the first moments of the verbal stage of phonological development. She presents phonological, morphological and lexical linguistic abilities typical of 2-3-year-old children with typical development. Her linguistic profile has been observed in language delay and in children under 3;6 years with Down syndrome. Determining the linguistic characteristics of SWH is essential for speech therapy intervention.